Optical properties of annealed Si:H thin film prepared by layer-by-layer (LBL) deposition technique - Goh, Boon Tong; Muhamad, Muhamad Rasat; Rahman, Saadah Abdul (Elsevier, 2010)
Optical studies were performed on annealed hydrogenated silicon (Si:H) thin films deposited by plasma-enhanced chemical vapor deposition (PECVD) using the layer-by-layer (LBL) deposition technique. The films were annealed for 1 h at temperatures of 400, 600, 800 and 1000 degrees C in ambient nitrogen. The effects of annealing temperatures on the optical properties, such as the optical-energy gap, Urbach energy, refractive index, dispersion energy and single oscillator strength, were studied. These parameters were determined from optical transmission and reflection spectroscopy. X-ray diffraction (XRD) and optical reflectance measurements were performed on the samples, showing the onset of transformation from an amorphous to a crystalline phase in the film structure when annealed at a temperature of 800 degrees C. The films were of mixed phase, with nanocrystalline grains embedded in the amorphous matrix. (C) 2010 Elsevier B.V. All rights reserved.